Unresolved Complexity in the Gene Regulatory Network Underlying EMT - Lavin, Deborah P.; Tiwari, Vijay K. (Frontiers in Oncology, 2020)
Epithelial to mesenchymal transition (EMT) is the process whereby a polarised epithelial cell ceases to maintain cell-cell contacts, loses expression of characteristic epithelial cell markers, and acquires mesenchymal cell markers and properties such as motility, contractile ability, and invasiveness. A complex process that occurs in various contexts during development and many disease states, EMT involves a plethora of transcription factors (TFs) and signalling pathways. Whilst great advances have been made in both our understanding of the progressive cell-fate changes during EMT and the gene regulatory networks that drive this process, there are still critical gaps in our knowledge. Epigenetic modifications are dynamic, chromatin modifying enzymes are vast and varied, transcription factors are pleiotropic, and signalling pathways are multifaceted and rarely act in isolation. Therefore, it is highly timely and of great importance that we decipher and understand each intricate step of the process and how these players at different levels crosstalk with each other to successfully orchestrate EMT. A delicate balance and fine-tuned cooperation of gene regulatory mechanisms is required for EMT to occur successfully, and until we resolve the unknowns in this network we cannot hope to develop effective therapies against diseases that involve aberrant EMT such as cancer. In this review, we focus on data that challenge these unknown entities underlying EMT, starting with EMT stimuli followed by intracellular signalling through to epigenetic mechanisms and chromatin remodelling.